2017
DOI: 10.1038/cddiscovery.2017.72
|View full text |Cite
|
Sign up to set email alerts
|

Akt1 and Akt3 but not Akt2 through interaction with DNA-PKcs stimulate proliferation and post-irradiation cell survival of K-RAS-mutated cancer cells

Abstract: Akt1 through the C-terminal domain interacts with the DNA-dependent protein kinase catalytic subunit (DNA-PKcs) and stimulates the repair of DNA double-strand breaks (DSBs) in K-RAS-mutated (K-RASmut) cells. We investigated the interactions of distinct domain(s) of DNA-PKcs in binding to full-length Akt1. Similarly, we analyzed potential interactions of DNA-PKcs with Akt2 and Akt3. Finally the effect of Akt isoforms in cell proliferation and tumor growth was tested. We demonstrated that Akt1 preferentially bin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
42
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(43 citation statements)
references
References 28 publications
1
42
0
Order By: Relevance
“…Next, we specifically investigated the role of Akt isoforms on YB-1 phosphorylation in MDA-MB-231 and MDA-MB-453 cells using a genetic approach. In MDA-MB-231 cells, each Akt isoform was stably knocked down with shRNA, as reported previously [ 44 ]. The Western blot and related densitometry values presented in Figure 3 C indicate that the level of P-YB-1 was not significantly affected after knockdown of any of the Akt isoforms.…”
Section: Resultsmentioning
confidence: 99%
“…Next, we specifically investigated the role of Akt isoforms on YB-1 phosphorylation in MDA-MB-231 and MDA-MB-453 cells using a genetic approach. In MDA-MB-231 cells, each Akt isoform was stably knocked down with shRNA, as reported previously [ 44 ]. The Western blot and related densitometry values presented in Figure 3 C indicate that the level of P-YB-1 was not significantly affected after knockdown of any of the Akt isoforms.…”
Section: Resultsmentioning
confidence: 99%
“…In NHEJ-mediated repair of DSBs, DNA-PKcs is a crucial player, and Akt was described to be involved in activating DNA-PKcs after irradiation-induced DNA damage [12,37]. Phosphorylation of the residues T2609 and S2056 is activating DNA-PKcs, and an indicator for efficient DSB repair capacity.…”
Section: Bez235 Suppresses Nhej Due To An Impaired Phosphorylation Ofmentioning
confidence: 99%
“…Akt exerts an important regulatory role in the repair process of DSBs via the NHEJ pathway [12,13,15,19,20]. Likewise, our laboratory presented the first evidence for a potential involvement of Akt in HR-repair [16].…”
Section: Importance Of Akt1 and Akt2 For Hr Repair Of Dsbsmentioning
confidence: 70%
“…In fact, upregulation of Akt-signaling is a feature of various tumor entities [10]. Furthermore, PI3K/Akt signaling and especially Akt through its isoforms Akt1 and Akt3-has been shown to play a regulatory role in the DNA damage response of tumor cells through the NHEJ [12,13,15,26] and potentially HR repair mechanisms [27,28]. Toulany et al, and others [12,15,29] have demonstrated that Akt1 and Akt3 can stimulate DNA-DSB repair through NHEJ, which results in radio-resistance of non-small cell lung cancer cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation